Elucidation of the chromatographic enantiomer elution order for praziquantel: An experimental and theoretical assessment. Issue 3 (15th January 2020) - Silva, Camilla Fonseca; do Nascimento, Tienne Aparecida; Guimarães, Luciana; Borges, Keyller Bastos; Nascimento, Clebio Soares
Abstract: In this work, we have studied both experimentally and theoretically the praziquantel (PZQ) chiral discrimination. According to the main results, the enantioseparation of PZQ was efficiently optimized by HPLC on the reverse phase from the Chiralpak IB column, which has cellulose tris (3, 5‐dimethylphenylcarbamate) (CDMPC) as a chiral selector. The thermodynamic and structural parameters obtained via density functional theory (DFT) calculations pointed out the chiral discrimination as well as the enantiomeric elution order of PZQ, thus elucidating the experimental data and validating our proposed method. Finally, the hydrogen bonds and π‐π stacking interactions played a key role in the discrimination between the PZQ diastereomeric complexes formed. Abstract :